Timely diagnostics and treatment of hypothyroidism is a basis for normal physical and psychical development of children (part 1) - V. V. Smirnov; A. I. Ushakov (Лечащий Врач)
Hypothyroidism belongs to widespread endocrine diseases. Disorders in the functions of various organs and systems causes difficulties in timely revealing of this diagnosis. The article analyzes the syndromes with which this pathology has to be differentiated. The algorithm of laboratory and instrumental diagnostics and treatment principles are presented.